Pursuit of a sustainable tourism policy by connecting historical sites and ancient conventions in Seoul - OH, LEE JONG (Advances in Social Sciences Research Journal, 2019)
Gyeongbokgung Palace is the most visited historical site in Seoul. With Gyeongbokgung Palace in the middle, Jongmyo Shrine is located to the left on Jongno 5-ga and Sajikdan Altar to the right in Sajik-dong. Currently, two events take place here—changing of the guards at Gyeongbokgung Palace and a memorial rite at Jongmyo Shrine—buttheyare conducted separately, whichindicates the lack of focus in explaining the connection between Seoul’s historical sites and history. Historical content that can be used to address this includes the procession of the king of Joseon and jikso activities by Joseon’s people. Jiksois a way to appeal directly to the king instead of a state agency about the people’s problems. The king’s ceremonial walk from the palace can be linked to Jongmyo Shrine, Sajikdan Altar, and the Cheonggyecheon Stream,Joseon’s busiest areas. Moreover, historical scenes of communication between the king and people can be recreated in spaces between the palace, Jongmyo Shrine, Sajikdan Altar, and Cheonggyecheon. This example will serve the history and sustainability of the city’s capital. Therefore, the present study utilized the Smart Seoul Map operated by the Seoul Metropolitan Government to identify the locations of Seoul’s important historical sites and analyze their distribution and scopes of influence and, consequently, identify places that can be utilized as new historical content. Determining how to link the king of Joseon’s ceremonial walk and jibs to historical places will help develop historical content to connect historical sites and small cities. This will enable the development of large-scale historical content that links the unit areas outside small cities as well as creation of a new type of urban culture while preserving Seoul’s historical nature.